Metaheuristic Guided Secured Transmission of E-Prescription of Dental Disease - Dey, Joydeep; Karforma, Sunil; Sarkar, Arindam; Bhowmik, Anirban (International Journal of Computer Sciences and Engineering, 2025)
This paper presents a novel and secured approach of transmission using the Cuckoo search metaheuristic algorithm. Dental disease is mostly caused by the colonization of the bacteria inside the oral cavity. Colonization of bacteria affects our teeth, gums, nerves, etc. Such patients are very common and to be cured appropriately. If left untreated, it may lead to severe damages inside the oral cavity. Cardiovascular and metabolic activities are also affected due to dental diseases. To transmit such information of any patient, here an encryption technique has been proposed preceded by generation of suitable key. Fittest session key has been generated by implementing the Cuckoo search metaheuristic algorithm. A mask matrix has been created for the proposed ciphering technique. Patient’s E-prescription proposed by the dentist would be fragmented into multiple fragments. In this paper, serial test has been used for testing the robustness of key and test results obtained reflects the good randomness in nature.